2014
DOI: 10.1021/cb500162w
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin, Diabetes, and Amyloid: Re-examination of the Inhibition of Amyloid Formation by Aspirin and Ketoprofen

Abstract: The loss of β-cell function and β-cell death are key features of diabetes. A range of mechanisms are thought to contribute to β-cell loss, including islet amyloid formation by the neuropancreatic hormone amylin (islet amyloid polypeptide, IAPP). Islet amyloid deposition also contributes to the failure of islet transplants. There are no therapeutic strategies for the treatment or prevention of islet amyloidosis. Aspirin and the nonsteroid anti-inflammatory drug (NSAID) ketoprofen, at clinically relevant doses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…Along with the weak affinity of aspirin for IAPP monomer ( Fig. 1 ), our simulation results are consistent with the latest experimental observation that aspirin had little inhibitive effect on IAPP aggregation 20 34 . In contrast, in the presence of curcumin and resveratrol the peptide chains made fewer contacts with each other.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Along with the weak affinity of aspirin for IAPP monomer ( Fig. 1 ), our simulation results are consistent with the latest experimental observation that aspirin had little inhibitive effect on IAPP aggregation 20 34 . In contrast, in the presence of curcumin and resveratrol the peptide chains made fewer contacts with each other.…”
Section: Resultssupporting
confidence: 91%
“…In this work, we applied atomistic discrete molecular dynamics (DMD) simulations to investigate the molecular mechanism of the inhibitory effects of two anti-aggregation molecules: curcumin and resveratrol. Interestingly, an early experimental study reported that aspirin, a structural derivative of phenol, had an inhibitory effect on IAPP aggregation 33 , however, no inhibition by aspirin was found in later studies by two different groups 20 34 . As a control, we also studied the effect of aspirin on hIAPP aggregation.…”
mentioning
confidence: 99%
“…In order to examine whether the inhibition presented by the polyphenol compounds was a result of their interaction with the metabolite amyloid structures, it was crucial to examine the possible activity of a compound that is known to be ineffective as an amyloid formation inhibitor. For this purpose, we used acetylsalicylic acid (ASA), a small-molecule applied to treat pain, fever, and inflammation, which has been previously used as a negative control for amyloid inhibitors of the IAPP amyloid polypeptide, and did not affect the amyloid formation process 16,49 . When tested as an inhibitor of metabolite amyloid formation, ASA did not affect aggregation, even at the highest concentration used for the other inhibitors, as was observed using ThT fluorescence assay, TEM imaging and the SH-SY5Y neuronal cell culture ( Supplementary Fig.…”
Section: Ultrastructural Analysis Of the Effect Of Polyphenols Onmentioning
confidence: 99%
“…Amyloid deposits localized in the islets involve the misfolding of islet amyloid polypeptide (IAPP) and contribute to the progression of type 2 diabetes in human and diabetes mellitus in adult cats (Hoppener et al 2002;Jaikaran and Clark 2001;O'Brien et al 1993;Westermark et al 2011). The effect of aspirin and ketoprofen were examined in pancreatic amyloidosis (Tu et al 2014). However, these drugs failed to inhibit amyloid formation or to disaggregate preformed fibrils (Tu et al 2014).…”
Section: R a F Tmentioning
confidence: 99%
“…The effect of aspirin and ketoprofen were examined in pancreatic amyloidosis (Tu et al 2014). However, these drugs failed to inhibit amyloid formation or to disaggregate preformed fibrils (Tu et al 2014). …”
Section: R a F Tmentioning
confidence: 99%